Original Research: TikTok's 'Dancing Nurses' During the COVID-19 Pandemic: A Content Analysis. Issue 12 (December 2022) - Lancaster, Rachelle; Sanchez, Michelle; Maxwell, Kelly; Medley, Rachel
ABSTRACT: Background: Amid the challenges of the ongoing COVID-19 pandemic, health care workers are using social media to publish increasing numbers of posts, memes, and videos. On TikTok, a rapidly growing and widely used social networking platform, videos labeled "dancing nurses" have recently been trending. Whether nurses or the general public consider such videos to breach professional ethical standards is unknown. Purpose: The aim of this study was to analyze and describe the use of the social media platform TikTok by nurses whose videos featured dancing nurses during the ongoing pandemic. Methods: Between March 1 and December 31, 2020, we conducted a search on TikTok using terms such as dancing nurse and hashtags such as "#dancingnurse." For each identified video, the numbers of followers, views, likes, concurrent COVID-19 morbidity and mortality rates, and other data were collected. For videos meeting the inclusion criteria, content analysis was performed to evaluate dancing nurse behaviors and apply the American Nurses Association (ANA) Code of Ethics for Nurses with Interpretive Statements, ANA social networking principles, and National Council of State Boards of Nursing social media guidelines. Results: A total of 52 videos met all inclusion criteria and were included for analysis. These videos had a mean of 1.51 million views each. Among these videos, there were 356 violations of Code of Ethics provisions, social networking principles, and social media guidelines. Forty of the videos (77%) included a choreographed dance; 24 (46%) contained twerking and three (6%) featured dance moves such as pelvic thrusts and gyrations. Conclusion: The findings offer insight into how nurses are using TikTok, specifically with regard to posting videos that feature dancing nurses. Some of the analyzed videos included content that could be construed, in our view, as inappropriate and even sexually suggestive. The concern is that such videos could damage the professional image of nurses and downplay the seriousness of the current pandemic. It's essential that nurses who use social media consider the content and presentation of what they post. There is an urgent need for nurses to understand professional and workplace guidelines and policies regarding the use of social media, and how these may apply to content developed and posted on platforms such as TikTok. Abstract : The authors examine the use of TikTok by nurses who incorporate dance into their videos—with a focus on understanding how nurses' use of social media might be violating professional ethical standards.